OrthoMTAtm A Newly Developed Mineral Trioxide Aggregate (MTA) Cements in Outpatients Attending Public Oral Health Korean Adolescents - Ah-Hyeon KIM; Youn-Soo SHIM; Jun-Sang YOO; Deog-Gyu SEO; Je-Seon SONG; So-Youn AN (Tehran University of Medical Sciences, 2016)
OrthoMTAtm A Newly Developed Mineral Trioxide Aggregate (MTA) Cements in Outpatients Attending Public Oral Health Korean Adolescents